Comparison of Political and Legal Dynamics in the Impeachment Process: A Case Study of Indonesia and Brazil - Rivera, Kevin; Iqbal Mustapa, Muhammad (Estudiante Law Journal, 2025)
Impeachment is a constitutional mechanism in presidential systems designed to hold presidents accountable, yet its execution is often shaped by political dynamics rather than purely legal considerations. This study compares the impeachment cases of Indonesia’s President Abdurrahman Wahid (2001) and Brazil’s President Dilma Rousseff (2016), revealing how political interests significantly influenced both processes. In Indonesia, Wahid’s removal stemmed largely from executive-legislative tensions and party-political maneuvering, with weak legal grounds. In Brazil, Rousseff’s impeachment was driven by intense government-opposition conflict, amplified by media narratives and public opinion, leading to heightened polarization. Despite constitutional frameworks, both cases illustrate how impeachment can be weaponized as a political tool rather than a legal safeguard. The study highlights the blurred boundary between law and politics in impeachment proceedings and underscores its consequences for democratic stability and institutional credibility. Findings suggest that when impeachment is motivated by partisan agendas, it risks eroding public trust in legal institutions and weakening governance. To preserve democratic integrity, impeachment processes must adhere to principles of objectivity, transparency, and fairness, ensuring they serve accountability not political expediency.